2016
DOI: 10.1002/cphc.201600821
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of a Dual‐Cation Ionomer Electrolyte

Abstract: The poly(N ) Li [AMPS] ionomer system (AMPS=2-acrylamido-2-methylpropane sulfonic acid) with dual cations has previously shown decoupled Li ion dynamics from polymer segmental motions, characterized by the glass-transition temperature, which can result in a conductive electrolyte material whilst retaining an appropriate modulus (i.e. stiffness) so that it can suppress dendrite formation, thereby improving safety when used in lithium-metal batteries. To understand this ion dynamics behavior, molecular dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We hypothesized that the strong interactions between lithium ions and ether oxygen atoms may cause an unexpected recoupling of the lithium diffusion dynamics with the polymer segmental motion, and this conclusion was supported by molecular dynamics (MD) simulations of similar ionomers . MD simulations of Li and Na ionic polymers with different compositions of co-cations were able to elucidate possible decoupling mechanisms and optimum compositions and sizes of the organic cation. , As shown in Figure , when the ratio of the Li ion to the ammonium co-cation is increased to 1:1 (vs 1:5), a hopping mechanism involving rearrangement of the Li coordination environment is possible along an interconnected cluster. This is believed to be the origin of the decoupling of the alkali metal cation from the bulk polymer dynamics.…”
Section: Anionic Single-ion Conductorsmentioning
confidence: 91%
See 1 more Smart Citation
“…We hypothesized that the strong interactions between lithium ions and ether oxygen atoms may cause an unexpected recoupling of the lithium diffusion dynamics with the polymer segmental motion, and this conclusion was supported by molecular dynamics (MD) simulations of similar ionomers . MD simulations of Li and Na ionic polymers with different compositions of co-cations were able to elucidate possible decoupling mechanisms and optimum compositions and sizes of the organic cation. , As shown in Figure , when the ratio of the Li ion to the ammonium co-cation is increased to 1:1 (vs 1:5), a hopping mechanism involving rearrangement of the Li coordination environment is possible along an interconnected cluster. This is believed to be the origin of the decoupling of the alkali metal cation from the bulk polymer dynamics.…”
Section: Anionic Single-ion Conductorsmentioning
confidence: 91%
“…24 MD simulations of Li and Na ionic polymers with different compositions of co-cations were able to elucidate possible decoupling mechanisms and optimum compositions and sizes of the organic cation. 25,26 As shown in Figure 3, when the ratio of the Li ion to the ammonium co-cation is increased to 1:1 (vs 1:5), a hopping mechanism involving rearrangement of the Li coordination environment is possible along an interconnected cluster. This is believed to be the origin of the decoupling of the alkali metal cation from the bulk polymer dynamics.…”
Section: "Mixed" Co-cation Approach To Decouple Li/na-ion Transport F...mentioning
confidence: 99%
“…Although the low ionic conductivity hinders the application of anionic polymer electrolytes, its single ion conducting nature still makes this class of materials a favorite research area. One way to tune their ionic conductivities can be achieved through replacing a fraction of the alkali metal ions with a co‐cation, e.g., a bulky quaternary ammonium ionic liquid cation, or adding a neutral plasticizer molecule, as demonstrated both experimentally and computationally . MD simulations revealed that the size and amount of the co‐cation have a different effect on ionic interactions and transport within the solid electrolyte.…”
Section: Simulation‐assisted Design Of New Solid‐state Electrolytesmentioning
confidence: 99%
“…On one hand, the increased ammonium improved the total ionic conductivity due to the plasticizing effect, and on the other hand it disrupted ion aggregation and thus reduced the ability for Li + hopping. Therefore, an intermediate ammonium concentration of 50 mol% was suggested to maximize Li + ion conduction . Furthermore, it was also found that the size of the ammonium cation affects alkali metal ion diffusion; the larger ammonium cations led to more disruption of ion aggregation, and therefore the smaller ammonium cation is a better option to achieve higher conductivity in these systems …”
Section: Simulation‐assisted Design Of New Solid‐state Electrolytesmentioning
confidence: 99%
“…Noor et al selected poly(2-acrylamido-2-methyl-1-propane-sulfonate) (PAMPS) homopolymer [609] or PAMPS with polyvinyl sulfonate [610] as a polymer backbone. With the addition of a small amount of a tetraglyme plasticizer, the conductivity reached 10 −5 S cm −1 at 50 °C; however, tetraglyme displays no effect on the Li + dynamics in PAMPS-based ionomers, the reasons for which have been explained by molecular dynamics calculations [611,612,613]. Usually, these polymers are tested in Na/Na symmetric cells to verify their compatibility with sodium.…”
Section: Sodium-ion Batteriesmentioning
confidence: 99%